2001
DOI: 10.1123/pes.13.4.402
|View full text |Cite
|
Sign up to set email alerts
|

Leisure-Time Internet Use Does Not Correlate with Physical Activity or Physical Fitness Level of Ninth Grade African-American Girls

Abstract: We assessed leisure-time Internet use (IU) and its relationship to physical fitness (PF) and leisure-time physical activity (PA) among 295 adolescent African-American girls. In addition, scales measuring variables in the Theory of Reasoned Action (TRA) were administered to elucidate PA data. Based on responses to the IU Questionnaire, participants were placed into either an Internet Nonuser (n = 184) or Internet User (n = 111) group. PF was assessed using body mass index (BMI) and AAHPERD Youth Fitness Tests. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 11 publications
4
16
1
Order By: Relevance
“…However, as opposed to not being encouraged, these particular sedentary behaviors should be balanced with the concomitant promotion of leisure-time physical activity. Our findings (i.e., body fat, mean = 30.0) support the current literature with respect to average obesity levels among minority females and are similar to a previous study that reported body fat averaging 33% among a population of urban African-American adolescent girls of similar age (19). In this study, body fat, the sum of the mean skinfold thicknesses, and body mass index did not correlate with either leisure-time physical activity, television watching time, Internet use time, or the sum of television watching time and Internet use time.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, as opposed to not being encouraged, these particular sedentary behaviors should be balanced with the concomitant promotion of leisure-time physical activity. Our findings (i.e., body fat, mean = 30.0) support the current literature with respect to average obesity levels among minority females and are similar to a previous study that reported body fat averaging 33% among a population of urban African-American adolescent girls of similar age (19). In this study, body fat, the sum of the mean skinfold thicknesses, and body mass index did not correlate with either leisure-time physical activity, television watching time, Internet use time, or the sum of television watching time and Internet use time.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have found no significant relationship between sedentary behavior and leisure-time physical activity in similar aged populations (19,4,26). This is somewhat surprising since logic dictates that the more leisure-time expended being sedentary, the less leisure-time is available for physical activity.…”
Section: Sedentary Behavior Operationalized As the Sum Of Televisionmentioning
confidence: 69%
See 1 more Smart Citation
“…7 TV viewing, video/computer game use and physical activity In total, 33 studies [11][12][13]17,18,21,25,[30][31][32]36,38,39,46,[48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66] were located that presented a measure of association between physical activity and TV viewing, playing video games or computer use. Nine studies were excluded from analyses either because they had serious design limitations, 46,50,51 presented insufficient data for meta-analytic synthesis, 11,12,54 presented data on composite measures of sedentary behavior 49,52 or reported on special populations. 36 The remaining [24] studies presented data on [41] independent samples (the unit of analysis) and were included in the final analyses.…”
Section: Sample Characteristicsmentioning
confidence: 99%
“…These results contribute importantly to the basis for current public health recommendations to limit adolescent girls' daily exposure to not only TV watching but other forms of EM, including electronic games and Internet use, to a combined maximum of 2 hours. adolescent girls, 36 probably because the amount of EM captured by such activity is limited. To our knowledge, our study is the first to investigate the effects of combined exposure to a variety of EM forms and CRF in adolescent girls.…”
Section: Longitudinal Associations Between Electronic Media Exposure mentioning
confidence: 99%